Laser induced elastico mechano luminescence of SrAl2O4 : Eu phosphor - Prajapati, M K; Srivastava, A K; Raghuvanshi, D S (Recent Research in Science and Technology, 2012)
When γ – irradiated elastic mechano luminescent materials SrAl2O4 : Eu are exposed to 1060 nm infrared pulse of nanosecond duration from CO2 laser, then stress produced in the crystals excites visible luminescence due to piezoelectric field in SrAl2O4 : Eu phosphor because they are non – centro symmetric. In the present investigation SrAl2O4 : Eu crystals are given laser shocks and ML intensity recorded. During laser induced shocks, ML intensity increases linearly with stress and attains a peak value at a particular time and then decays exponentially with time. A theoretical approach has been proposed to explain the experimental results.